UKURAN PASAR UKURAN PASAR (Market Size) DAN INVESTASI ASING LANGSUNG DI ASEAN - Lumadya, Adi (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2016)
The main objective of this study was to examine the influence of some economic variables that include market size proxied with income per capita, economic growth, and exports to the Foreign Direct Investment in the member countries of ASEAN-9. The analytical tool used is the Least Squares Regression (Ordinary Least Square) and Panel Data. In the Data Panel will look for similarities in effect is Fixed (Fixed Effect) and the effect is Random (Random Effect). The results of the analysis are: Based on the analysis of OLS concluded that the variable size of the market (market size) were proxied with Per Capita Income (GDPP), Economic Growth (EG), and exports (EG) significantly affects the Direct Foreign Investment. Based on the analysis of Panel Data with Fixed Effect Method concluded that the variable size of the market (market size) were represented with per capita income (GDP), Economic Growth (EG), and exports (EG) significantly affects the Direct Foreign Investment. Based on the analysis of Panel Data with Random Effect method concluded that the variable size of the market (market size) were proxied with per capita income (GDP), Economic Growth (EG), and exports (EG) significantly affects the Direct Foreign Investment. Keywords: Foreign Direct Investment, Fixed Effect, Random Effect